Determinants of Corporate Cash-holding Levels: An Investigation of the US Retail Industry - Zhang, Yuan (2012)
This study investigates the determinants of cash-holdings levels in the US retail industry. The sample contains 706 firms in a 20 year period of 1992 to 2011. This study employed an eight-variable model to determine whether these variables exerted a significant impact on the level of cash holdings in the US retail industry- the eight variables are, investment opportunity, firm size, cash flow, leverage, bank debt, liquid asset substitutes, capital expenditure and dividend pay-out. The study found that investment opportunities had a significantly positively relationship to the level of cash holdings, whilst firm size, bank debt, liquid asset substitutes and dividend pay-out has a significantly negatively relationship to cash holdings. The results provided support for the trade-off theory and the transaction motive and the precautionary motive in relation to level of cash-holdings in the US retail industry.